Triplet-state dynamics of a metalloporphyrin photosensitiser (PtTMPyP4) in the presence of halides and purine mononucleotides. - KELLY, JOHN MOFFAT (My University, 2011)
The photophysical properties of Pt(ii) meso-tetrakis(4-N-methylpyridyl) porphyrin (PtTMPyP4) have been investigated in the presence of purine mononucleotides using emission and transient UV/visible/near-IR spectroscopy. While both adenosine 5?-monophosphate (AMP) and guanosine 5?-monophosphate (GMP) form 1:1 and 1:2 complexes with PtTMPyP4, the effect on the triplet lifetime is different. With AMP, complexation gives rise to an enhancement of lifetime and quantum yield due to shielding from dissolved oxygen and a slight decrease in the non-radiative decay rate. When complexed with GMP, quenching is observed consistent with photoinduced electron transfer from guanine to triplet-excited PtTMPyP4, due to both dynamic quenching of the porphyrin and to short-lived emission from 1:1 (67 ns) and 1:2 (400 ns) complexes. No charge-separated photoproducts are observed by transient UV/vis/near-IR absorption spectroscopy on the nanosecond timescale, suggesting that rapid reverse electron transfer may prevent type 1 DNA damage.
PUBLISHED
Keywords: 5'-Guanylic Acid; Adenosine Monophosphate; DNA Damage; Halogens; Metalloporphyrins; Organoplatinum Compounds; Oxygen; Photosensitizing Agents; Quantum Theory; Spectrophotometry, Infrared; Spectrophotometry, Ultraviolet; 5'-Guanylic Acid; Adenosine Monophosphate; DNA Damage; Halogens; Metalloporphyrins; Organoplatinum Compounds; Oxygen; Photosensitizing Agents; Quantum Theory; Spectrophotometry, Infrared; Spectrophotometry, Ultraviolet